The Acti-Pair program helps men with prostate cancer increase physical activity with peer support: a mixed method pilot study - Amandine Baudot; Amandine Baudot; Amandine Baudot; Amandine Baudot; Nathalie Barth; Nathalie Barth; Nathalie Barth; Nathalie Barth; Claire Colas; Claire Colas; Maël Garros; Arnauld Garcin; et al. (Frontiers Media S.A., 2024)
BackgroundAlthough the health benefits of physical activity (PA) are recognized, prostate cancer patients do not follow PA recommendations. Barriers to PA, whether physical, environmental or organizational, are known. Furthermore, even when these barriers are overcome, this achievement is not systematically accompanied by lifestyle change. Many strategies have shown to be effective in increasing patient adherence to PA. This study aims to assess the feasibility and the viability of the Acti-Pair program which combines three strategies: peer support, a personalized and realistic PA project, and support from health and adapted physical activity professionals in a local context.Methods and analysisWe conducted a pilot study utilizing a mixed qualitative and quantitative methodology, employing feasibility and viability assessments. Quantitative assessments included recruitment, retention adherence rates, process and potential effectiveness (PA and motivation) indicators; while qualitative methods were used to evaluate the program's practicality, suitability and usefulness. Indicators of potential effectiveness were assessed before and after the intervention using a Wilcoxon test for matched data. Qualitative data were collected through semistructured interviews conducted by two researchers with various program stakeholders. The study lasted for 3 years.ResultsTwenty-four patients were recruited over a 25-month period. Forty-two percent of patients completed the program 3 months after the beginning. We recruited 14 peers and trained nine peers over a 10-month period. The program was coordinated extensively by adapted PA professionals, while health professionals were involved in recruiting patients and peers. Self-reporting of moderate to vigorous PA was increased after the Acti-Pair program initiation [42.86 (30.76) at baseline to 53.29 (50.73)]. Intrinsic motivation significantly increased after participation in the Acti-Pair program [1.76 (1.32) before the intervention vs. 2.91 (1.13) after the intervention]. The key player to support the Acti-Pair program in the field has been the PA support system. The main challenge has been the difficulty of health professionals in promoting PA.DiscussionThis pilot study has shown that the Acti-Pair program is feasible and viable. It will allow us to extend the peer support intervention to other contexts and assess the effectiveness of this intervention and its generalization.